Analisis Kualitas Ragi Roti Sourdough pada Berbagai Jenis Tepung dengan Penambahan Ekstrak Tomat (Solanum lycopersicium) - Dewi, Putri Rosfiana; Sari, Laela Dwi Kartiko; Windayanti , Aridha Elfarikha; Cica, Siska Aliatuliyah; Nikmah, Alvi Lailatun; Isnawati , Isnawati (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
Sourdough yeast is a natural yeast for making bread that aims to slow down the decay process. The fermentation process can be assisted by using tomato extract. This study aims to obtain the best quality yeast from various types of flour with the addition of tomato extract (Solanum lycopersicum). This experimental study was designed with independent variables in the form of flour types (wheat, wheat, glutinous rice), control variables in the form of tomato extract and the ratio of material composition (1:1), and response variables in the form of yeast quality (color, odor, shape, presence of foreign objects, and yeast activity). Data were analyzed descriptively and compared with yeast quality standards based on SNI (Indonesian National Standard). The results showed that wheat flour produced the best sourdough yeast. The results showed that wheat flour met the yeast requirements based on SNI 01-2982-1992, had a yellowish white color with a normal odor, good acidity, in the form of coarse powder with no foreign objects and good yeast activity. Unlike wheat flour, which has a brownish white color, a very sour normal odor, a coarse powdery texture, and no foreign objects, but its activity is not good so it does not meet the SNI 01-2982-1992 standard. Glutinous rice flour is white, has a slightly sour normal odor, a fine powdery form, and no foreign objects, its activity is very good, but does not meet the SNI 01-2982-1992 standard because of its color and texture.